Age estimation in forensic investigations using tooth cementum annulations and pulp to tooth area ratio - Athira, C P; Murthy, Sarvani; Naveen Kumar, R K; Niveditha; Indu Sundaram, T S; Jose, Jithin (Journal of Indian Academy of Forensic Medicine, 2021)
Forensic age estimation is beneficial in the process of identification of deceased in mass disasters and in determining age for social  benefits, license and legal requirements. This study aims to compare two methods of age estimation; the tooth cementum annulations  (TCA), and, pulp to tooth area ratio (PTR), in terms of reliability and correlation with actual age. Mandibular first premolar teeth  which were used for the estimation of age using cementum annulations, were obtained from thirty patients undergoing therapeutic  extraction for orthodontic treatment. For the same patients mandibular canine and premolar radiographs were also obtained with prior  informed consent and were employed for age estimation using pulp to tooth area ratio. Mandibular first premolar teeth were sectioned  for visualization of cemental annulations using phase contrast microscope. Number of TCA was added to the average age of eruption  to estimate the age of individual. Mandibular canine and first premolar radiographs were taken using paralleling technique and PTR  was estimated using Autocad 2007 software. TCA using phase contrast microscopy was found to be a highly reliable method for age  estimation in comparison to PTR (p=0.000). When all the parameters used in the study were combined by multiple regression  analysis, highest accuracy of age estimation with least standard deviation of 1.86 years was obtained. Age estimation from tooth  cementum annulations is more accurate when compared with pulp to tooth area ratio. The combination of different methods will  provide more reliability in age estimation as compared to relying upon a single method.
Keywords: Age estimation; Tooth cementum annulations; Pulp to tooth area ratio